Towards Effective Upper Basic Education Curriculum Implementation in Private and Public Schools in Nigeria - Michael Hangeior Saaondo; Bonaventure Chia; Ellah Barnabas (Journal of Research in Science and Mathematics Education (J-RSME), 2023)
Purpose: This study investigated the effective implementation of the upper basic education curriculum in private and public schools in Nigeria. Methodology: The research employed a cross-sectional survey design, guided by three research questions and three null hypotheses. The study used a sample of 1134 respondents, comprising 954 teachers and 180 supervisors, drawn from a population of 145,783 teachers and 19,466 supervisors. Findings: A multistage sampling technique was adopted. The researchers developed an instrument named the Questionnaire on the Implementation of Upper Basic Education Curriculum (QIUBEC) for data collection. Significance: Three experts validated the instrument, and it demonstrated a reliability coefficient of 0.98 using Cronbach's Alpha. Mean, percentage, and standard deviation were employed to address the research questions, and a t-test was utilized to test the null hypotheses at a 0.05 level of significance. Based on the findings, several recommendations were made, including the suggestion that science teachers should choose teaching pedagogies that provide all students in the classroom with equal learning opportunities to reach their full potential.